2020
DOI: 10.1002/rcm.8679
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of sunscreen compounds by liquid chromatography/high‐resolution tandem mass spectrometry

Abstract: Rationale Exposure to UV light can induce adverse effects on human health, such as photo‐aging, immunosuppression, and cancer. Sunscreens are used to prevent the absorption of UV rays, but certain UV‐filtering compounds have been shown to disrupt endocrine systems or act as carcinogens. To assess the effects of the exposure to such compounds, it is important to study the pathways by which they are biotransformed in the body. Methods Liquid chromatography coupled to high‐resolution tandem mass spectrometry (LC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Use of the interim iTTC for the metabolites will depend on if there are existing toxicity data and/or PK data or suitable toxicological analogues for the metabolites. All of the case study chemicals, except for ecamsule, could be metabolized by the skin and/or in the systemic circulation (Guesmi et al 2020). As such, use of the interim iTTC would require consideration of the internal exposure to parent and metabolite, except for ecamsule, since it is not metabolized (according to internal unpublished data and the summary in DrugBank).…”
Section: Results For Case Study Chemicalsmentioning
confidence: 99%
“…Use of the interim iTTC for the metabolites will depend on if there are existing toxicity data and/or PK data or suitable toxicological analogues for the metabolites. All of the case study chemicals, except for ecamsule, could be metabolized by the skin and/or in the systemic circulation (Guesmi et al 2020). As such, use of the interim iTTC would require consideration of the internal exposure to parent and metabolite, except for ecamsule, since it is not metabolized (according to internal unpublished data and the summary in DrugBank).…”
Section: Results For Case Study Chemicalsmentioning
confidence: 99%
“…Homosalate is metabolized primarily to 3,3,5-Trimethylcyclohexanol and salicylic acid in human and rat liver microsomes ( Guesmi et al , 2020 ). The 3,3,5-trimethylcyclohexanol was not active in any of the ED assays.…”
Section: Resultsmentioning
confidence: 99%
“…The identity of plasma and urinary metabolites of the 6 UV filters were taken from literature sources based on in vitro , animal, and human studies and evaluated for activity in ToxCast/Tox21 database ( Bury et al , 2019a , b , c ; Guesmi et al , 2020 ; Hiller et al , 2019a , b ; Huang et al , 2019 ; Klotz et al , 2019 ; Okereke et al , 1993 ; Tarazona et al , 2013 ). Specifically, the metabolites identified in the references and assessed were: (1) salicylic acid and 2-ethylhexanol for octisalate, (2) salicylic acid and 3,3,5-trimethylcyclohexanol for homosalate, (3) ethyl 2-cyano-3,3-diphenylacrylate the analog of 2-cyano-3,3-diphenylacrylic acid for octocrylene, (4) 2,4-dihydroxybenzophenone (DHB), 2,2′-dihydroxy-4-methoxybenzophenone (DHMB), and 2,3,4-trihydroxbenzophenone (THB) for oxybenzone, and (5) 4-methoxycinnamic acid and 2-ethylhexanol for octinoxate.…”
Section: Methodsmentioning
confidence: 99%
“…UV filters are designed for external application on the skin; however, previous studies have shown that they can be absorbed through the skin, further metabolized, and eventually bioaccumulated or excreted [ 58 ]. To more thoroughly assess the effects of the human exposure to such compounds, it is important to study the pathways by which they are biotransformed in the body [ 40 , 59 ]. HLMs represent an affordable in vitro alternative for xenobiotics such as drugs and cosmetic ingredients biotransformation studies.…”
Section: Discussionmentioning
confidence: 99%